The Role of Internal Control System on Characteristics of Village Financial Reports - M. Muslim, Ratna Sari (Jurnal Akuntansi, 2021)
This study aimed to examine and analyze the effect of the Village Financial System, the Capacity of the village apparatus, and the internal control system has a significant positive effect on village financial reports inflation characteristics. In addition, it was also meant to test and analyze the influence of the internal control system as a moderating relationship between the Village Financial System and the Capacity of the village apparatus and characteristics of village financial reports. The samples of forty-four respondents. This study indicated that the Village Financial System, the Capacity of the village apparatus and internal control system, has a significant positive effect on village financial reports' inflation characteristics. At the same time, the internal control system shows no influence, unable to moderate the relationship between the Village Financial System and the Capacity of the village apparatus and the characteristic.